Kejadian penyakit kulit di Desa Asir-Asir Asia Kecamatan Lut Tawar Kota Takengon Kabupaten Aceh Tengah - Neni Ekowati Januariana; Al Chairi (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Skin diseases can be caused by several factors, namely living habits and the environment. Skin diseases can develop in personal hygiene and poor environmental hygiene conditions. The diversity of types of skin diseases and the factors that cause skin diseases requires a deeper study of every skin disease phenomenon that occurs in the community. This study aims to determine the factors that cause skin diseases in Asir-Asir Asia Village, Lut Tawar District, Takengon City, Central Aceh Regency. This research was carried out using descriptive analytic in the form ofa survey to determine the factors that cause skin disease in Asir-Asir Asia Village, Lut Tawar District, Takengon City, Central Aceh Regency. The results showed that residents with personal hygiene were 37 people (41.11%) and people with poor personal hygiene were 53 people (58.89%). Respondents who have environmental sanitation by meeting health requirements are 16 people (17.78%) and as many as 74 respondents (82.22%) do not meet health requirements and respondents with the category of having skin disease complaints are observed subjectively and objectively as many as 60 respondents (66.67%) and have no complaints of skin disease as many as 30 respondents (33.33%). The conclusion in this study is that personal hygiene factors have a significant relationship with the incidence of skin disease complaints with a significant value of 0.008 (p < 0.05) and environmental sanitation factors also have a significant relationship with the incidence of skin disease complaints with a significant value of 0.001 (p <0.05).